Pre-service and in-service Elementary School Teacher’s Procedural and Representational Knowledge of Fractions - Samar Tfaili (Eximia, 2025)
The main purpose of this study is to assess pre-service and public elementary mathematics school teachers’ conceptual understanding and computational abilities of fractions. 20 pre-service mathematics teachers and 24 in-service mathematics teachers participated in this study. In-service teachers were divided into two categories; one for teachers having a degree in mathematics and the other for teachers having a degree in any other discipline. Results showed that both pre-service and in-service teachers’ computational knowledge is greater than their representational knowledge. However, in-service teachers had difficulties in multiplication of mixed numbers (41.7% correct answers). The study revealed that regarding the computational knowledge no significant difference was found between in-service and pre-service teachers. When considering representational abilities, pre-service teachers were able to perform better than in-service teachers. The difference was significant (p<0.005). however, when we compared preservice teachers’ performance to in service teachers who graduated from the faculty of pedagogy, there was no significant difference (p=0.717). Moreover, faculty of pedagogy graduate in-service teachers performed better than preservice teachers which shed a light on the importance of teachers’ specialization even in elementary classes.